2021
DOI: 10.21037/tp-20-358
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting successful use of intranasal dexmedetomidine: a cohort study from a national paediatrics tertiary centre

Abstract: Background: Use of intranasal (IN) dexmedetomidine for procedural sedation has been reported in recent years. Good patient selection is important to ensure high success rates. We aimed to identify factors that influence the successful use of IN dexmedetomidine in non-invasive investigations. Methods: All paediatric patients who received IN dexmedetomidine for investigations between 01 July 2019 to 01 July 2020 were included. Baseline demographics, time to reach adequate sedation level, duration of sedation, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The studies were quite homogenous in terms of the administered dose, most of the authors used 3 μg/kg to induce sleep. Fan et al [ 12 ], using this dosage, reported adequate sedation for ABR but noted significant differences in weight and age between babies who were adequately sedated by IN DEX only and the ones who did not; however, adequate sedation was obtained more frequently in ABR than other procedures investigated in this study, suggesting the IN DEX to be particularly suitable for this use case. A single dose appears to be sufficient to achieve sedation in the majority of cases, and multiple administrations can be given, if necessary, without adverse effects; the maximum dosage more often reported is 100 μg.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The studies were quite homogenous in terms of the administered dose, most of the authors used 3 μg/kg to induce sleep. Fan et al [ 12 ], using this dosage, reported adequate sedation for ABR but noted significant differences in weight and age between babies who were adequately sedated by IN DEX only and the ones who did not; however, adequate sedation was obtained more frequently in ABR than other procedures investigated in this study, suggesting the IN DEX to be particularly suitable for this use case. A single dose appears to be sufficient to achieve sedation in the majority of cases, and multiple administrations can be given, if necessary, without adverse effects; the maximum dosage more often reported is 100 μg.…”
Section: Discussionmentioning
confidence: 56%
“…Reynolds [ 20 ] showed a high number of satisfactory sedation from a single dose (89%); the same author in a prospective and randomized study [ 6 ], showed the ability to complete ABR examination with one sedative dose was 91%. Similarly, Baier et al [ 19 ] found a 90% success rate by the first dose, Godbehere et al [ 4 ] identified a 100% success rate, and Fan et al [ 12 ] reported 83% sedation success. Conversely, Li et al [ 21 ] described a lower success rate (64.3%) compared with the results of other authors.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations